Strength analysis of a regenerative flow compressor and a pump based on fluid-structure coupling. (2022) - Kumar, Mahendhar; Venkateshwaran, Akash; Pavan Kumar, Machavolu Sai Santhosh; Sreekanth, Manavalla; Jebaseelan, Davidson; Sivakumar, R.
Abstract: Regenerative flow pumps and compressors are low specific speed roto-dynamic turbomachines capable of producing high heads at low specific speeds. The present study focuses on the flow characteristics of both the turbomachines viz. a compressor and a pump and extended to investigate the structural integrity for the considered flow condition. CFD solver, ANSYS FLUENT was used to perform the flow simulation. The simulation is performed with pump running at 2900 rpm and compressor with 100, 000 rpm to achieve a pressure ratio of about 3 in both cases. The influence of centrifugal force, pressure load and fluid temperature from the aerodynamic analysis are applied to the impeller blade and hub to perform the Fluid-Structure Interaction (FSI) in the FEA module of the software. From the CFD simulation it is observed that a maximum pressure of about 0.29 MPa in pump, 0.24 MPa in compressor and a maximum temperature of 562 °C in the case of compressor occur close to the outlet for both the turbomachinery. The Mach number is found to be around 2.5 in the compressor and 0.01 in the pump. For the stress assessment, the maximum von Mises stress in the blades is compared to the maximum allowable stress of grey cast Iron. Radial displacements were also considered to determine the structural integrity from the stress analysis. It is predicted that maximum stresses are induced on the blades near the outlet and hence the failure is expected to occur on the blades. The combined effect of varying pressure load, fluid temperature, and centrifugal forces with deformation and stress in both pump and compressor were also presented. This paper highlights the aero-mechanical features of the regenerative flow compressor and pump obtained from numerical simulations, which are expected to provide a sound basis for further investigations.